Revisión del método de valoración contingente: experiencias de la aplicación en áreas protegidas de América Latina y el Caribe - Garzón, Lina Paola (2013)
The environmental goods and services cannot be valued through markets economically defined. Therefore, it has been necessary to implement methodologies such as contingent valuation for this purpose. This method was proposed 66 years ago and it has been widely used in different fields such as conservation of protected areas. The aim of this article is to provide a theoretical review of the contingent valuation method and to show experiences of its application in the assessment of Protected Areas in Latin America. In the sixties and seventies contingent valuation began to acquire greater importance for estimates of non-use values. Then, there was a cross-disciplinary integration of elements to strengthen the development of surveys and in the nineties appeared a criticism of its validity .Moreover, contingent valuation studies in Latin American countries have had positive results in determining the willingness to pay for recreational value, environmental services value, social benefits and public management of protected areas.